The Evaluation of Kurikulum Merdeka with Context Input Process Product (CIPP) Model - Fitri, Zayyana Zahrotul; Sukiman, Sukiman; Nurusshoimah, Nurusshoimah (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2024)
Structured curriculum evaluation is part of advancing education in a country. Because of its efforts, it can improve the curriculum in the development stage as well as those that have been implemented. Thus making education in the country more prepared in the future. The purpose of this study is to determine the readiness of the implementation of a kurikulum merdeka in terms of context, input, process, and obstacles in its implementation. The method used is a qualitative method with research subjects in the form of teachers and students. Data collection techniques through curriculum documents, photos of activities, and questionnaire data of TK Plus An-Nur Peterongan. Analysis techniques by sorting data, presenting data, and drawing conclusions. The results of the research from the aspects of context, input, and process show that TK Plus An-Nur Peterongan is overall ready to implement a kurikulum merdeka with an independent category of change. This is evidenced by the results of the analysis of school needs to achieve educational goals, locally charged learning activities, strengthening the Pancasila student profile project, literacy, STEAM, ethical values, and identity through the intracurricular and extracurricular learning process and cooperation with the community environment. The obstacles to the implementation of the kurikulum merdeka found in the evaluation of the CIPP model seen from the input aspect are the quality of teachers who are not from the Kindergarten department and learning resources or media that are not fulfilled for the introduction of numerical literacy. This research contributes in the form of understanding and advice to teachers that evaluating the curriculum used by schools with the CIPP model can determine the readiness of the school or an obstacle in implementing the curriculum.